2020
DOI: 10.22271/chemi.2020.v8.i6ab.11048
|View full text |Cite
|
Sign up to set email alerts
|

Studies on correlation and path coefficient analysis in foxtail millet [Setaria italica (L.) BEAUV]

Abstract: The present investigation consists of 40 genotypes of Foxtail Millet, which were grown in the Field Experimentation Centre of the Department of Genetics and Plant breeding, SHUATS, Prayagraj during Kharif 2019 following RBD with three with three replications. The data were recorded on 13 characters to study the analysis of variance, heritability, genetic advance, coefficient of variation, correlation coefficient and path analysis. Based on the mean performance genotype ISE1419, were identified as best genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…In the genotypic correlation (Table 5), characters such as days to 50% flowering (0.344), days to maturity (0.451), plant height (0.403), flag leaf area (0.775), peduncle length (0.351), panicle length (0.672) have shown a high significant positive correlation with the grain yield. Similar results were reported with Brunda et al [1][2][3], Ayesha et al [26], Kumawat et al [28], Pallavi et al [4].…”
Section: Studies On the Association Of The Characterssupporting
confidence: 90%
See 2 more Smart Citations
“…In the genotypic correlation (Table 5), characters such as days to 50% flowering (0.344), days to maturity (0.451), plant height (0.403), flag leaf area (0.775), peduncle length (0.351), panicle length (0.672) have shown a high significant positive correlation with the grain yield. Similar results were reported with Brunda et al [1][2][3], Ayesha et al [26], Kumawat et al [28], Pallavi et al [4].…”
Section: Studies On the Association Of The Characterssupporting
confidence: 90%
“…The highest positive direct effect was shown by panicle length (0.444) and the lowest direct effect was shown by number of productive tillers (-0.0999). Similar results were reported with Brunda et al [1][2][3], Ayesha et al [26], Kumawat and Sharma [28], Pallavi et al [4].…”
Section: Studies On the Association Of The Characterssupporting
confidence: 90%
See 1 more Smart Citation
“…A significant positive correlation between plant height (r=0.57**) and flowering time (0.12**) with grain weight per plant in this present study is not desirable as higher yield will be followed by taller plants and longer flowering time. A significant positive correlation between plant height and flowering time with yield was also reported in previous studies in foxtail millet (Pallavi et al 2020) and rice (Asante et al 2019;Saha et al 2019;Sadimantara et al 2021;Prathiksha et al 2022). Therefore, multiple-traits selection using a weighted selection index is necessary to perform proper selection based on desired traits and to achieve the breeding objective.…”
Section: Correlations Analysis Of the F2 Population Of Iceri-5 And Bo...mentioning
confidence: 58%
“…Yield (grain weight per plant) is a complex trait that is largely influenced by many associated traits. The information on the strength and direction of correlation among traits to yield (grain weight per plant) would be useful in designing foxtail millet breeding program in particular for yield improvement (Pallavi et al 2020). The correlation analysis showed that a significant and positive correlation in the yield components was observed in the number of productive tillers (r = 0.30**), number of panicles per plant (r = 0.30**), and panicle weight per plant (r = 0.99**).…”
Section: Correlations Analysis Of the F2 Population Of Iceri-5 And Bo...mentioning
confidence: 99%